IoT-blockchain empowered Trinet: optimized fall detection system for elderly safety - Alfayez, Fayez; Bhatia Khan, Surbhi (Frontiers in Bioengineering and Biotechnology, 2023)
Numerous elderly folks reside alone in their homes. Seniors may find it difficult to ask for assistance if they fall. As the elderly population keeps growing, elderly fall incidents are becoming a critical public health concern. Creating a fall detection system for the elderly using IoT and blockchain is the aim of this study. Data collection, pre-processing, feature extraction, feature selection, fall detection, and emergency response and assistance are the six fundamental aspects of the proposed model. The sensor data is collected from wearable devices using elderly such as accelerometers and gyroscopes. The collected data is pre-processed using missing value removal, null value handling. The features are extracted after pre-processed data using statistical features, autocorrelation, and Principal Component Analysis (PCA). The proposed approach utilizes a novel hybrid HSSTL combines Teaching-Learning-Based Optimization (TLBO) and Spring Search Algorithm (SSA) to select the optimal features. The proposed approach employs TriNet, including LSTM, optimized Convolutional Neural Network (CNN), and RNN for accurate fall detection. To enhance fall detection accuracy, use the optimized CNN obtained through the hybrid optimization model HSSTL. Securely store fall detection information in the Blockchain network when a fall occurs. Alert neighbours, family members, or those providing immediate assistance about the fall occurrence using Blockchain network. The proposed model is implemented in Python. The effectiveness of the suggested model is evaluated using metrics for accuracy, precision, recall, sensitivity, specificity, f-measure, NPV, FPR, FNR, and MCC. The proposed model outperformed with the maximum accuracy of 0.974015 at an 80% learning rate, whereas the suggested model had the best accuracy score of 0.955679 at a 70% learning rate.